Infiltration of illegal immigrants and electoral politics in Assam - Ragi, Sangit Kumar (2016)
Infiltration from Bangladesh has been a major issue of controversy and ethnic conflicts in the state of Assam. Though a section of intelligentsia has been contesting the premise, government reports from time to time and studies have confirmed the massive illegal migration of population from across the international border in Assam. The settlement of these migrants in different parts of the State which largely have been concentrated along the border areas has changed the ethno-religious landscape of the region. The native and indigenous Assamese have a sense of fear that the rising swamp of migrants would not only dissolve the socio-culture identity of the ethnic Assamese in their own soil but would reduce their political preponderance in the State in times to come. Since the last four decades they have been demanding the sending back of illegal immigrants and deregistering their names from electoral rolls. On the other hand, migrants now with their names on the electoral rolls have emerged as a numerically significant block to decide the electoral outcomes in several assembly and parliamentary constituencies. While in the beginning they stayed as backbone of the electoral strength of the Indian National Congress, gradually they have started flexing their political muscle in the system. A large chunk of their population gravitated towards the All India United Democratic Front (AIUDF) led by Badrudin Ajmal which aims to polarise them to their side on religious lines. The article, besides dealing with the issues and debates pertaining to infiltration, seeks to analyse how it has transformed the electoral politics of the State in the last few decades. Election results have been taken into account to underscore the changing electoral dynamics in the State. - Reproduced.
Keywords: Elections - India - Assam; Immigrants - India - Assam; Immigrants